Tumor progression and metastatic dissemination in ovarian cancer after dose‐dense or conventional paclitaxel and cisplatin plus bevacizumab. Issue 9 (7th August 2018) - Bizzaro, Francesca; Falcetta, Francesca; D'Agostini, Elisa; Decio, Alessandra; Minoli, Lucia; Erba, Eugenio; Alessandro Peccatori, Fedro; Scanziani, Eugenio; Colombo, Nicoletta; Zucchetti, Massimo; Bani, Maria Rosa; Ubezio, Paolo; et al.
Abstract : The efficacy of therapeutic regimens incorporating weekly or every‐3‐weeks paclitaxel (PTX) for ovarian cancer is debated. We investigated the addition of bevacizumab in regimens of chemotherapy with different PTX doses and schedules in preclinical models. Treatments were cisplatin (DDP) with weekly PTX (conventional), or dose‐dense‐equi (every other day to the conventional cumulative dose), or dose‐dense‐high (total dose 1.5 times higher), with or without bevacizumab. Treatment efficacy was evaluated analyzing tumor growth in different time‐windows in two patient‐derived ovarian cancer xenografts with different sensitivity to cisplatin. Tumor progression, metastasis and survival were studied in ovarian cancer models growing orthotopically and disseminating in the mouse peritoneal cavity. Short‐term effects on cell cycle, tumor cell proliferation/apoptosis and vasculature were evaluated by flow cytometry and immunohistochemistry. PTX dose‐dense (with/without DDP) was superior to the conventional scheme in a dose‐dependent manner; the high efficacy was confirmed by the lower ratio of tumor to normal cells. All schemes benefited from bevacizumab, which reduced tumor vessels. However, DDP/PTX dose‐dense‐high (only chemotherapy) was at least as active as DDP/PTX conventional plus bevacizumab. DDP/PTX dose‐dense‐high plus bevacizumab was the most effective in delaying tumor progression, though it did not prolong mouse survival and the continuous treatment with bevacizumab was associated with a malignant disease. These findings indicate that the effect of bevacizumab in combination with chemotherapy may depend on the schedule‐dose of the treatment and help to explain the unclear benefits after bevacizumab. Abstract : What's new? Patients with ovarian cancer typically receive platinum‐ and taxane‐based therapies; recently, bevacizumab, the monoclonal antibody against VEGF, has been incorporated into these regimens. The benefit of bevacizumab in regimens of chemotherapy incorporating dose‐dense paclitaxel (PTX) for ovarian cancer is still debated, however. Taking together the results of four preclinical trials in ovarian cancer xenograft models, here the authors found that the advantage of bevacizumab in combination regimens depends on the schedule‐dose of chemotherapy. Furthermore, the quantitative analyses of tumor growth in different time‐windows was linked to biological end‐points and provided new insights into the different outcomes.